Validity analysis of the mathematical literacy test: implementation of the pancasila student profiles in instrument development - Nurul Afni Sinaga; Yulia Zahara; Zurra Yusally Aufa; Novilia Junianti Saragih (LPPM Universitas Malikussaleh, 2024)
The background to this research is based on the need to improve students' mathematical literacy skills, which are integrated with character formation based on Pancasila values. This research aims to analyze the validity of the mathematics literacy test implemented with the Pancasila student profile in developing test instruments. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, with a focus on validation of the instruments developed. The instrument consists of 20 questions that were validated by media experts, material experts, and language experts. The research results show that media validation, material validation, and language validation are in the very valid category. Of the 20 questions, 1 question item was declared valid in the very high category, 2 questions were valid in the high category, 14 questions were valid in the medium category, and 3 questions were valid in the low category. The reliability of the instrument is classified as high with a value of 0.783. Apart from that, 7 questions have good differentiating power, while 13 questions have sufficient differentiating power. Based on the level of difficulty, 4 questions are in the difficult criteria, 14 questions are in the medium criteria, and 4 questions are in the easy criteria. These results indicate that the mathematical literacy test instrument developed generally has good validity and reliability and can be used as an effective measuring tool in evaluating students' mathematical literacy abilities, as well as integrating the values ​​of the Pancasila student profile.